A model intercomparison study of climate change‐signals in extratropical circulation - Rauthe, Monika; Hense, Andreas; Paeth, Heiko (International journal of climatology, 2004)
Since 1970, the observed time series of various extratropical circulation modes have revealed remarkable trends. In many studies it has been suggested that these trends may be related to global warming due to increasing greenhouse gas (GHG) concentrations. Coupled climate model scenario experiments may give a hint of such a relationship. Here, a large model intercomparison study is presented, incorporating most state‐of‐the‐art models of the international modeller community with GHG and GHG plus sulphate aerosol (SUL) forcing, in order to quantify the signals common to different climate models and to determine the degree of uncertainty. The extratropical circulation candidates are the Arctic oscillation (AO), the North Atlantic oscillation (NAO), the Aleutian low (AL) and the Antarctic oscillation (AAO). Most climate models agree in predicting positive AO and AAO trends into the 21st century, these being different from the respective results of long‐term control experiments. The NAO appears to be less sensitive to radiative forcing, with slightly positive and negative trends occurring in different models. The AL tends to strengthen in several models with GHG + SUL forcing. Projecting the spatial structure of the circulation modes onto the trend patterns of mean sea‐level pressure (SLP) indicates that, in particular, the AO and AAO contribute considerably to the simulated long‐term trends in SLP. Intermodel variations in Northern Hemisphere SLP trends become predominantly apparent over the mountainous regions and the North Pacific. In the Southern Hemisphere, the Antarctic region is subject to large model uncertainties. The multi‐decadal trends of all circulation modes except the NAO are statistically significant in the majority of the climate‐change experiments. At the interannual time scale, external radiative forcing does account for a small but statistically significant part of total multi‐model variability, but this part is of the same order of magnitude as the systematic differences between the models. At decadal time scales, the external impact clearly stands out from the other sources of variability. Present‐day climate models mostly agree in predicting a strengthening of the annular modes AO and AAO. As all models generally project a deepening of SLP over the polar caps, time series indicative of these regions might be a more appropriate measure of the sensitivity of extratropical circulation. Copyright © 2004 Royal Meteorological Society